The Relationship between Consumer Sentiment, Government Expenditure, and Private Consumption in Six Main Asian Countries - Meiyu LU (Communications of International Proceedings, 2023)
In recent years, there have been many kinds of research surrounding the impact of government spending on private consumption. One of the main controversies is whether the impact of government spending on private consumption is positive or negative. At the same time, sentiment factors (e.g., consumer confidence) have been increasingly considered in economic decision-making. However, fewer research has been conducted to consider sentiment factors together with government spending and private consumption. This paper aims to perform the Granger causality test using panel data to find the causal relationship between the three variables mentioned above. Empirically, we found that Consumer confidence index (CCI) is the Granger cause of Private consumption (PC) and Government spending (GS). At the same time, GS can also affect the PC. Besides, we use LLC, IPS, and Fisher's panel unit root test to check the stationarity of the variables. We employ Kao, Pedroni, and Westerlund method to perform panel cointegration test. Our results suggest that all variables pass the panel unit root and panel cointegration test in the case of first-order difference. The results indicate a long-term stationary relationship between CCI, PC and GS for the selected countries.
Keywords: Asia; Consumer confidence; Government spending; Private consumption; Panel data; Granger causality test; Panel unit root test; Panel cointegration test.